2015
DOI: 10.7314/apjcp.2015.16.3.1181
|View full text |Cite
|
Sign up to set email alerts
|

BreastLight Apparatus Performance in Detection of Breast Masses Depends on Mass Size

Abstract: Background: Accurate measurement of breast mass size is fundamental for treatment planning. We evaluated performance of BreastLight apparatus in detection breast of masses with this in mind. Materials and Methods: From July 2011 to September 2013, a total of 500 women referred to mammography unit in Yazd, Iran for screening were recruited to this study. Performance of BreastLight in detection breast masses regard their sizeing, measured with clinical breast examination (CBE), mammography and sonography, was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…[3] Evaluation of 310 patients between 2012 and 2013 in Cairo reported much better results with the breast light, with sensitivity, specificity, positive predictive value, negative predictive value and total accuracy of 93.0%, 73.7%, 91.4%, 77.8% and 88.2%, respectively. [4] Shiryazdi et al [5] concluded in another Iranian study that the performance of the breast light in detection of lesions ≤1 cm assessed by CBE, mammography and sonography was 4.4%, 7.7% and 12.5%, respectively, and for masses >4 cm, 65%, 100% and 57.1%. [5] The performance of the breast light in detection was significantly increased with larger masses (p<0.001), which once again challenges the notion that this device can be used as a screening tool equivalent to mammography.…”
Section: Breast Lightmentioning
confidence: 99%
See 1 more Smart Citation
“…[3] Evaluation of 310 patients between 2012 and 2013 in Cairo reported much better results with the breast light, with sensitivity, specificity, positive predictive value, negative predictive value and total accuracy of 93.0%, 73.7%, 91.4%, 77.8% and 88.2%, respectively. [4] Shiryazdi et al [5] concluded in another Iranian study that the performance of the breast light in detection of lesions ≤1 cm assessed by CBE, mammography and sonography was 4.4%, 7.7% and 12.5%, respectively, and for masses >4 cm, 65%, 100% and 57.1%. [5] The performance of the breast light in detection was significantly increased with larger masses (p<0.001), which once again challenges the notion that this device can be used as a screening tool equivalent to mammography.…”
Section: Breast Lightmentioning
confidence: 99%
“…[4] Shiryazdi et al [5] concluded in another Iranian study that the performance of the breast light in detection of lesions ≤1 cm assessed by CBE, mammography and sonography was 4.4%, 7.7% and 12.5%, respectively, and for masses >4 cm, 65%, 100% and 57.1%. [5] The performance of the breast light in detection was significantly increased with larger masses (p<0.001), which once again challenges the notion that this device can be used as a screening tool equivalent to mammography. The most recent publication found was in 2015 in the Indian Journal of Cancer, where only 35.8% of lesions that were detected by mammography were detected by the breast light.…”
Section: Breast Lightmentioning
confidence: 99%
“…A tool that is portable and battery operated will facilitate its use in remote locations in the developed world as well as in low and middle-income countries. [28,[32][33][34][35]37] The complete wish-list of the requirements of a practical tool for the rapid diagnosis of breast cancer is shown in Table 1.…”
Section: Portabilitymentioning
confidence: 99%
“…Transillumination Imaging has been studied extensively for breast cancer screening in Egypt, Iran, Iraq, and Ghana. [28,29,[31][32][33][34][35] While DOI is still lab-based, it is touted to be a promising technique to be used for breast cancer screening in the future. [43,80] The DOI system is classified as parallel plate geometry, bed-based, and handheld probe techniques, based on the arrangement of the source and detector.…”
Section: Spectroscopy Based Techniques To Diagnose Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation